2011
DOI: 10.1017/s0022112010005501
|View full text |Cite
|
Sign up to set email alerts
|

A falling cloud of particles at a small but finite Reynolds number

Abstract: International audienceThrough a comparison between experiments and numerical simulations, we have examined the dynamics of a cloud of spheres at a small but finite Reynolds number. The cloud is seen to flatten and to transition into a torus, which further widens and eventually breaks up into droplets. While this behaviour bears some similarity to that observed at zero inertia, the underlying physical mechanisms differ. Moreover, the evolution of the cloud deformation is accelerated as inertia is increased. Two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(26 citation statements)
references
References 11 publications
2
24
0
Order By: Relevance
“…As the viscosity of the fluid for Re = 0.05 is much larger than the viscosity for Re = 50, columns at large Re in the absolute frame will experience a faster dynamics. These results are qualitatively comparable to those of Pignatel et al [6], which showed that increasing Re enhances effective cohesion and slows the falling of spherical clouds of particles. Figure 2 shows the time variation of the center of mass V mass reduced by a corrected characteristic velocity of the column U cyl .…”
supporting
confidence: 91%
See 2 more Smart Citations
“…As the viscosity of the fluid for Re = 0.05 is much larger than the viscosity for Re = 50, columns at large Re in the absolute frame will experience a faster dynamics. These results are qualitatively comparable to those of Pignatel et al [6], which showed that increasing Re enhances effective cohesion and slows the falling of spherical clouds of particles. Figure 2 shows the time variation of the center of mass V mass reduced by a corrected characteristic velocity of the column U cyl .…”
supporting
confidence: 91%
“…Therefore, many investigations were done in order to better understand the behavior of these particle-laden flows, presenting a large panel of geometries such as jets, streams, drops, and spherical clouds. The sedimentation of spherical clouds of particles, in an external fluid of variable viscosity, has been recently investigated experimentally and numerically [6]. With the exception of the experimental work of Nicolas [7], investigations related to jets or column of particles focused mainly on highly viscous fluids (i.e., zero Reynolds numbers limit) [8,9], air, and moderate vacuum (large Reynolds numbers limit) [10][11][12] or other kinds of interactions: capillary bridges, van der Waals forces [13-16], etc.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A “cloud” is defined as a very larger number of particles surrounded by clear fluid [112,113,114,115,116,117,118,119,120,121,122,123,124,125,126]. A cloud of droplets can be treated as a single droplet ( i.e.…”
Section: Studies Of Toxic Aerosols From Inhaled Cigarette Smokementioning
confidence: 99%
“…Among the various intriguing phenomena they observed is the well-known cascade of falling plumes, which often occur during the descent of heavy drops [2][3][4]. Similar Rayleigh-Taylor-type instabilities also arise for heavy suspension droplets [2,5,6]. Heavy particles inside the drop can lead to formation of a Hill-type vortex, with a toroidal structure which can become destabilized to form localized plumes.…”
Section: Introductionmentioning
confidence: 99%